Does Emigration Drain Entrepreneurs? - Massimo Anelli; Gætano Basso; Giuseppe Ippedico; Giovanni Peri (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Emigration of young, motivated individuals may deprive countries-of-origin of entrepreneurs. We isolate exogenous variation in a large emigration wave from Italy between 2008 and 2015 by interacting diaspora networks with economic pull factors in destination countries, and find that larger emigration rates reduced firm creation and innovative start-ups. We estimate that for every 100 emigrants, 26 fewer firms were created. An accounting exercise shows that 37 percent of the effect was due to the disproportionate loss of young people. The remaining effect was due to selection into emigration of highly entrepreneurial individuals, as well as negative spillovers on firm creation.
Keywords: J61; H70; O30; M13; 330; emigration; demography; brain drain; entrepreneurship; innovation; EU integration